Influence of rearing conditions on reproduction, growth, milk yield and quality of meat and milk of sheep and goats - Hristov Slavča; Stanković Branislav; Nakov Dimitar; Milošević-Stanković Ivana; Maksimović Nevena (Biotechnology in Animal Husbandry, 2020)
The most important stressors in our country are unfavourable climatic and nutritional conditions. Extreme deviations in climatic and nutritional conditions are immediate stressors for the body of sheep and goats. Appetite in sheep and goats decreases if they are exposed to extremely high ambient temperatures, while cold increases the body's energy needs and leads to the mobilization of fat from body fat and the consequent oxidation of fat and the formation of non-esterified fatty acids. Thyroid activity is reduced when these animals are exposed to high temperatures, and increased when they are exposed to cold. In an environment with high temperatures, blood glucose and cholesterol concentrations decrease due to unsuccessful maintenance of homeostasis. Sheep and goats are naturally kept in a group, which basically protects them from predators. They successfully register the action of new stimuli, especially noise and sudden movements of nearby predators. Early weaning breaks the bond between mother and offspring and adversely affects the development of normal behavioural relationships in lambs and kids, because artificial feeding systems do not fully meet the needs of oral activity, so sucking of the umbilical and scrotal region often occurs. Investigations of the influence of various technological procedures on the reactivity of the adrenal cortex indicate that the separation of the animal from the herd and immobilization are the most significant stimuli. Electrical stunning of sheep at the slaughterhouse causes significant stimulation of the sympathetic system with a sudden release of adrenaline and noradrenaline. In conditions of intensive production, the most significant stressors and physiological conditions that lead to stress are: parturition, birth, puerperal period, weaning, oestrus, high pregnancy, various surgical procedures, veterinary and zootechnical procedures, extreme variations of microand macroclimatic conditions, variations in quantity and food quality, etc.